Geometric parameters affecting seismic fragilities of curved multi-frame concrete box-girder bridges with integral abutments. (1st September 2016) - Jeon, Jong-Su; DesRoches, Reginald; Kim, Taesik; Choi, Eunsoo
Highlights: Seismic fragility assessment for curved multi-frame RC box-girder bridges. A detailed three-dimensional finite element model of curved bridges. Identification of vulnerable components of curved bridges using fragility function. Impact of horizontal curvature, abutment skew, and column height on fragilities. Abstract: The current study presents the effect of geometric parameters such as horizontal curvature, abutment skew, and column height on the seismic response and fragility of curved multi-frame concrete box-girder bridges with in-span hinges. For this purpose, two as-built bridges with integral abutments (two- and three-frame) with typical configurations of this class of bridges in California are selected to create a detailed three-dimensional inelastic model for each bridge. The model is used to perform a set of nonlinear time history analyses for a ground motion suite to compute the fragility function of components and system. Moreover, multiple levels of each geometric parameter are determined to identify the effect of geometry. As-built bridge models are modified by varying one of each parameter and the modified models are repeatedly simulated for the seismic fragility assessment. Outcomes are used to examine the above parameters affecting seismic demands and fragility curves for this class of bridges. It is observed that most geometric parameters significantly affect fragilities for some components, but not all system fragilities; the column height is the most influence parameter affecting the system fragility while the horizontal curvature and abutment skew have a relatively minimal influence on the system fragility of this class of bridges.